2021
DOI: 10.1111/ene.15000
|View full text |Cite
|
Sign up to set email alerts
|

Admission computed tomography radiomic signatures outperform hematoma volume in predicting baseline clinical severity and functional outcome in the ATACH‐2 trial intracerebral hemorrhage population

Abstract: Background and purpose: Radiomics provides a framework for automated extraction of high-dimensional feature sets from medical images. We aimed to determine radiomics signature correlates of admission clinical severity and medium-term outcome from intracerebral hemorrhage (ICH) lesions on baseline head computed tomography (CT). Methods:We used the ATACH-2 (Antihypertensive Treatment of Acute Cerebral Hemorrhage II) trial dataset. Patients included in this analysis (n = 895) were randomly allocated to discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Therefore, the application of radiomics can extract more objective features that are not retrievable based on vision and manual measurements. It has consistently been shown to be effective for the prediction of hematoma expansion and poor neurologic outcome in spontaneous IPH patients [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. As for traumatic IPH, we herein demonstrated its usefulness to further expand the limited evidence currently available [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the application of radiomics can extract more objective features that are not retrievable based on vision and manual measurements. It has consistently been shown to be effective for the prediction of hematoma expansion and poor neurologic outcome in spontaneous IPH patients [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. As for traumatic IPH, we herein demonstrated its usefulness to further expand the limited evidence currently available [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning models generated from selected radiomics features have been shown to correlate well with clinically important diagnostic or prognostic outcomes [ 20 ]. Focusing on spontaneous intracerebral hemorrhages, extensive studies have been performed, which demonstrated the good predictive capability of models derived from radiomics features for hematoma expansion [ 21 , 22 , 23 , 24 , 25 ] and poor neurological outcome [ 24 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, increased c-statistics were observed after the radiomics features were combined with clinical and radiological parameters constantly.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, radiomics software (Pyradiomics version 2.1.2) 13,14 was used to automatically extract n=14 shape features from ICH masks. [7][8][9][10][11] To mitigate the impact of CT data heterogeneity on the analysis, we adopted voxel dimension resampling of ICH masks and CT images to an isotropic voxel spacing of 1x1x1 mm using B-spline interpolation prior to shape feature quantification. [7][8][9][10][11][13][14][15] Figure 2 visualizes the segmentation workflow and ICH shape features.…”
Section: Hematoma Shape Feature Quantificationmentioning
confidence: 99%
“…[7][8][9][10][11] To mitigate the impact of CT data heterogeneity on the analysis, we adopted voxel dimension resampling of ICH masks and CT images to an isotropic voxel spacing of 1x1x1 mm using B-spline interpolation prior to shape feature quantification. [7][8][9][10][11][13][14][15] Figure 2 visualizes the segmentation workflow and ICH shape features. A list of all shape features is provided in Table 1.…”
Section: Hematoma Shape Feature Quantificationmentioning
confidence: 99%
See 1 more Smart Citation